SEARCH ALGORITHM FOR THE PARAMETRIC IDENTIFICATION OF THE ELECTRIC DRIVE OF THE MONITORING SYSTEM - A. S. Abufanas; A. A. Lobaty; A. G. Shvedko (Системный анализ и прикладная информатика)
The problem of parametric identification of a mathematical model of a technical system or a device is considered, which considers the electric drive of a monitoring system installed on an unmanned aerial vehicle. Identification of the parameters of elements of a complex technical system is an actual scientific task, since when developing a new technical system for its synthesis and research, it is necessary to have mathematical models of the elements of the system.It is proposed to solve the problem by applying the search gradient identification algorithm for a given objective residual function in the form of a difference in the output signal of the identified element of the system and its model. When solving the problem, the random character of the processes occurring in the system and at the output of the output signal meter is taken into account. The identification algorithm is developed on the basis of the representation of the model of parameters in the form of an ordinary vector-matrix equation, on the right side of which there is a model of the driving influence in the form of a given deterministic function of time. A general structural diagram of the parametric identification search system with a gradient algorithm is presented.As an example for evaluating the operability of the proposed algorithm, we consider the simplest model of an electric drive, given by a transfer function in the form of an inertial link. Qualitative illustrations of the operability of the proposed algorithm and quantitative characteristics of the signal and parameter changes of the identified object are presented.